2009
DOI: 10.1212/wnl.0b013e3181c34b34
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic nucleus stimulation in Parkinson disease induces apathy

Abstract: These preliminary results confirm the role of the subthalamic nucleus in associative and limbic circuitry in humans and suggest that it is a key basal ganglia structure in motivation circuitry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
125
1
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(144 citation statements)
references
References 33 publications
11
125
1
6
Order By: Relevance
“…However, positive correlations between apathy and prefrontal, temporal, parietal and limbic areas were also noted in some studies 14, 56, 57, 58. Studies using T1‐weighted imaging reported reduced GM thickness in the temporal lobes 62 or increased atrophy in the frontal and parietal lobes (e.g.…”
Section: Methodsmentioning
confidence: 96%
“…However, positive correlations between apathy and prefrontal, temporal, parietal and limbic areas were also noted in some studies 14, 56, 57, 58. Studies using T1‐weighted imaging reported reduced GM thickness in the temporal lobes 62 or increased atrophy in the frontal and parietal lobes (e.g.…”
Section: Methodsmentioning
confidence: 96%
“…A PET study investigated apathy in nondemented PD patients (Average disease duration at surgery was 11.2 years) after deep brain stimulation of the subthalamic nucleus using the Apathy Evaluation Scale [105]. In this study, positive correlations were identified between apathy scores and glucose metabolism in the frontal lobe; whereas, apathy scores were negatively correlated with glucose metabolism in the posterior cingulate gyrus and the frontal lobe [104]. A VBM study has shown evidence that in PD low grey matter density in many cortical brain region within the frontal, parietal, cingulate cortex correlated with high apathy scores [50].…”
Section: Apathymentioning
confidence: 99%
“…We found 7 studies that have investigated the underlying mechanism of apathy in PD using a variety of imaging techniques [45,50,66,67,93,101,104] (See table 4). A PET study investigated apathy in nondemented PD patients (Average disease duration at surgery was 11.2 years) after deep brain stimulation of the subthalamic nucleus using the Apathy Evaluation Scale [105].…”
Section: Apathymentioning
confidence: 99%
See 1 more Smart Citation
“…2 Several functional imaging studies 94,95 in patients with Parkinson's disease without dementia have supported this hypothesis, showing that these patients can present with abnormal activation at the level of the dorsolateral or ventrolateral prefrontal cortex and caudate nucleus during executive tasks. Results from glucose metabolism studies [96][97][98] with ¹⁸F-FDG PET in Parkinson's disease have shown that apathy severity is associated with metabolic activity in diff erent cognitive regions, including the inferior medial frontal gyrus, cingulate cortex, insula, cuneus, and tempo roparietal region.…”
Section: Lesions and Neuroimagingmentioning
confidence: 99%